STEM Program in Kindergarten in Australia and the possibility of benefiting from it in the Kingdom of Saudi Arabia - Alshehri, Tahani Mohammed Mougram (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the experience of STEM programs in early childhood education in Australia using the Comparative approach.The study concluded a number of findings, including, the initiation of STEM education in Australia at the early childhood stage and aims to provide children with fundamental concepts in the four domains through various innovative methods suitable for their age and level of development.The program emphasizes encouraging teachers to implement STEM by engaging them in initiatives, offering training programs and courses. The Australian government supports the implementation of STEM programs and provides initiatives. STEM programs in Australia focus on building foundational skills such as critical thinking, calculation, communication, collaboration, and creativity. They are implemented through various programs like " Let’s Count " "Little Scientists, " digital technology activities, "Bush Kinder, " and "ELSA, " all of which are integrated and based on the early learning framework. Based on the results, The Kingdom has made efforts to develop education and keep pace with modern programs, and Tatweer Company for Educational Services has launched the STEM scientific centers project. However, special programs for kindergarten should be reconsidered and allocated and the Ministry of Education in the Kingdom aims to strengthen cooperation with private schools. Some private schools implement the STEM program, however, these schools are few, and it is necessary to exert more efforts and attention to teaching this program in the Kingdom. In light of the results, the researcher recommends that the STEM program start from kindergarten in early education, setting the objectives of the STEM program in line with the standards and needs of children and providing the STEM program in an integrated manner.
Keywords: STEM Program; Kindergarten; Australia